Computational study of metal free alcohol dehydrogenation employing frustrated lewis pairs - Mane, Manoj V.; Rizvi, Masood A.; Vanka, Kumar (Journal of Organic Chemistry, 2015)
The catalysis of acceptorless alcohol dehydrogenation (AAD) is an important area of research. Transition metal-based systems are known to be effective catalysts for this reaction, but developing metal free catalytic systems would lead to highly desirable cheaper and greener alternatives. With this in mind, this computational study investigates design strategies than can lead to metal free frustrated Lewis pairs (FLPs) that can be employed for AAD catalysis. A careful study of 36 different proposed FLP candidates reveals that several new FLPs can be designed from existing, experimentally synthesized FLPs that can rival or be even better than state-of-the-art transition metal-based systems in catalyzing the alcohol dehydrogenation process.